Aging Challenges. Perceived Age - a New Predictor of Longevity? - S. A. Shalnova; N. A. Imaeva; A. E. Imaeva; A. V. Kapustina (Столичная издательская компания, 2022)
The ageing process is accompanied by the manifestation of many characteristics, so-called biomarkers, which can be quantified and used to assess a patient's health status. One of these signs is the progressive decline of a human's facial look, which is described by the concept of 'perceived age'. Facial aging is the most important parameter of perceived age. However, over the years, researchers have identified risk factors that affect the facial skin, including smoking, systematic consumption of alcoholic beverages, overweight or underweight, environmental conditions, and psychosocial determinants. The influence of psychological state on the appearance and life prognosis is shown. The authors presented data from the international literature on the study of perceived age. The frontiers of using perceived age as a biomarker of aging were Danish scientists who developed the main methodological approaches to determine this indicator. One such methodology used in population studies has been the clinical technique of assessing perceived age through photography. The review presents this methodology in detail, with its advantages and modifications. The authors conclude that the measurement of an individual's perceived age can serve not only as a prognostic indicator,  but also over time can become a   useful marker of the effectiveness of various treatments. Until now perceived age has hardly been studied in population studies, the authors presented data from the works of V.A.  Labunskaya, G.V.  Serikov,  T.A.  Shkurko who develop the direction related to psychology of perceived age  and in their studies use social-psychological approaches of appearance assessment.